2020
DOI: 10.1002/jdn.10072
|View full text |Cite
|
Sign up to set email alerts
|

BALB/c female subjected to valproic acid during gestational period exhibited greater microglial and behavioral changes than male mice: A significant contra intuitive result

Abstract: Most animal model studies of autism spectrum disorders (ASD) were performed in males. Thus, little is known about the mechanisms underlying disease progression in females. Here, we searched for potential influences of sex and environment on gestational valproic acid‐induced behavioral abnormalities using hippocampal‐dependent tasks, and on number and morphometry of microglia of the molecular layer of the dentate gyrus (Mol‐DG). We compared male and females BALB/c control mice with BALB/c mice gestationally exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The reduction in microglia number close to the time of insult we observe in our experiments is also in contrast to other studies in young adult animals at a time point after remodeling occurs in the brain. For example, increased microglial density has been reported in the molecular layer of the dentate gyrus in female BALBc mice at 5 months [ 19 ]. This is in contrast to studies by Kazlauskas et al, who showed no change in microglial density in the same molecular layer of the dentate gyrus; however, this was carried out in early neonatal (PD-7) development and in a different strain Cr1Fcen:CF1 lineage showing age-specific and strain specific effects of the drug [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in microglia number close to the time of insult we observe in our experiments is also in contrast to other studies in young adult animals at a time point after remodeling occurs in the brain. For example, increased microglial density has been reported in the molecular layer of the dentate gyrus in female BALBc mice at 5 months [ 19 ]. This is in contrast to studies by Kazlauskas et al, who showed no change in microglial density in the same molecular layer of the dentate gyrus; however, this was carried out in early neonatal (PD-7) development and in a different strain Cr1Fcen:CF1 lineage showing age-specific and strain specific effects of the drug [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both, the volume of the molecular layer and the number of microglial cells were considerably higher in VPA mice from standard cages. Mice housed in enriched cages presented less intense behavioral and cellular abnormalities [81].…”
Section: Neurodevelopmental Risksmentioning
confidence: 99%
“…Considering that most studies of ASD in experimental animals were brought about in males, Dos Santos et al [81] have decided to compare the effects of prenatal VPA exposure (600 mg/kg on gestational day 12.5) on behavioral abnormalities in male and female offspring (housed either in standard or enriched cages) with the use of hippocampal-related tasks in five-month-old animals. Also, the number and morphometry of microglial cells located in the molecular layer of the dentate gyrus were evaluated.…”
Section: Neurodevelopmental Risksmentioning
confidence: 99%
“…Numerous studies and reviews highlight the impaired behavioral phenotype in rodents prenatally exposed to VPA. Decreased exploration associated with locomotor hyperactivity and stereotypic-like behaviors and reduced social interactions were mainly observed in VPA-induced ASD-like behavior in rodents [ 144 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ] in a sex-dependent manner, which is often observed in individuals with autism [ 154 ] ( Table 5 ).…”
Section: Vpa-induced Autistic-like Behavior In Animalsmentioning
confidence: 99%